2014
DOI: 10.1016/j.virol.2013.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Conserved features of an RNA promoter for RNA polymerase II determined from sequence heterogeneity of a hepatitis delta virus population

Abstract: The right terminal domain of genomic hepatitis delta virus (HDV) RNA is involved in viral replication by recruiting host RNA polymerase II. To identify conserved features of this region, we performed high-throughput 454 sequencing of an HDV population actively replicating in cells. We generated 473,139 sequences representing 2351 new HDV variants of this region and investigated nucleotide conservation and positions of covariation in the population. We found that the sequence is heterogeneous and the rod-like c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Putative promoter regions have been identified on the HDV RNA sequence, mainly by chromatography affinity experiments . According to these studies, a terminal region of the pseudo–double‐stranded structure spanning nucleotides –1683 to 80 was compared for the 265 full‐length HDV genomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Putative promoter regions have been identified on the HDV RNA sequence, mainly by chromatography affinity experiments . According to these studies, a terminal region of the pseudo–double‐stranded structure spanning nucleotides –1683 to 80 was compared for the 265 full‐length HDV genomes.…”
Section: Resultsmentioning
confidence: 99%
“…The main posttranslational modification positions are indicated. At the top of the figure, a schematic representation of the HDV genome according to Beeharry et al is drawn. Red box highlights the studied region.…”
Section: Resultsmentioning
confidence: 99%
“…It seems to be the case for HDV mRNA (27), and a recent study has suggested that the 5'-end region of the HDAg mRNA, which coincides with one extremity of the rod-like genomic RNA and displays a complex secondary structure, may play an important role in HDV replication (80).…”
Section: Motifs For Transcription and Replication The Presence Of Trmentioning
confidence: 99%
“…HDV circulates as a “cloud” of virions that are different from each other but highly related, known as a quasispecies [ 11 , 12 ]. Study of viral quasispecies has been traditionally based on cloning and sequencing, and more recently on a more sensitive and reproducible method known as next-generation sequencing (NGS) [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Study of viral quasispecies has been traditionally based on cloning and sequencing, and more recently on a more sensitive and reproducible method known as next-generation sequencing (NGS) [ 13 15 ]. In HDV, this method has been used in samples derived from cell cultures [ 12 ], but never in clinical samples. The RNA evolution rate, defined as the rate at which RNA substitutions occur, is a useful parameter to understand viral adaptation to the host.…”
Section: Introductionmentioning
confidence: 99%